2010
DOI: 10.1021/nn102324e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate Alternatives for Drug Delivery

Abstract: The ability to apply nanomaterials as targeted delivery agents for drugs and other therapeutics holds promise for a wide variety of diseases, including many types of cancer. A nanodelivery vehicle must demonstrate in vivo efficacy, diminished or no toxicity, stability, improved pharmacokinetics, and controlled-release kinetics. In this issue, Lee et al. construct polymer nanobins that fulfill these requirements and demonstrate effective delivery of doxorubicin in vivo to breast cancer cells. This Perspective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
125
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(128 citation statements)
references
References 14 publications
0
125
0
Order By: Relevance
“…Recent studies show that packaging clinically approved drugs into nanoscale vesicular vehicles (10-100 nm in diameter) can effectively deliver chemotherapeutic drugs to tumour sites, leading to improved pharmacokinetic efficiency and therapeutic efficacy 1,2 . Nonetheless, these drug-loaded artificial nanoparticles have several disadvantages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that packaging clinically approved drugs into nanoscale vesicular vehicles (10-100 nm in diameter) can effectively deliver chemotherapeutic drugs to tumour sites, leading to improved pharmacokinetic efficiency and therapeutic efficacy 1,2 . Nonetheless, these drug-loaded artificial nanoparticles have several disadvantages.…”
mentioning
confidence: 99%
“…Nonetheless, these drug-loaded artificial nanoparticles have several disadvantages. First, nanometre-scale materials, as nonself components, are usually toxic and may cause adverse effects, for example, by activating oxidative stress pathways [2][3][4][5][6][7] ; second, micelles are of inadequate stability in the blood stream; third, co-encapsulation of more than one drug can result in batch-to-batch variability in the drug load; and fourth, the cost of assembly of nanoparticles is expensive, especially if they contain engineered antibodies or aptamers. Notwithstanding these defects, the development of advanced nanoparticle drug carriers is currently vigorously pursued in the field of cancer therapeutics 1,7 .…”
mentioning
confidence: 99%
“…Such nanomaterial-based drug delivery systems have shown improved therapeutic efficacy with lower unwanted adverse effects compared with conventional chemotherapy, at least in animal models (1)(2)(3)(4)(5). Despite the appreciable success of cancer nanomedicines in preclinical studies, only a few such agents have entered clinical trials, and fewer still have shown promising therapeutic outcomes and advanced to subsequent trial stages (6)(7)(8).…”
mentioning
confidence: 99%
“…However, these may be highly cytotoxic 44 and exhibit low colloidal stability. 45 A cationic polymer commonly studied for nucleic acid delivery, polyethyleneimine, also shows high toxicity and often must be chemically modified to ameliorate this before use, 46 as well as requiring high doses for effective knockdown. 47 Other studies using nonlipid formulations, like exosomes 48 or gold nanoparticle immobilization, 49 have also used much higher in vitro siRNA concentrations of up to 200 nM to achieve similar knockdown to the 60 nM reported here, while also using easier-to-transfect cell types like CHO-K1 or HeLa cells.…”
mentioning
confidence: 99%
“…It has also been speculated that surface adsorption or conjugation methods, while fairly effective, may have lower efficiency because of the reduced availability of immobilized siRNA. 50 Some siRNA delivery systems require added heat or chemicals during synthesis 45,51 that can be potentially destructive to siRNA. In contrast, the method described here allows for quick, simple complexation under mild conditions.…”
mentioning
confidence: 99%